Current knowledge of human Mpox viral infection among healthcare workers in Cameroon calls for capacity-strengthening for pandemic preparedness - Nka, Alex Durand; Bouba, Yagai; Fokam, Joseph; Ka'e, Aude Christelle; Gabisa, Jeremiah Efakika; Mandeng, Nadia; Mfonkou, Delors Jacques Toumansie; Ambe, Chenwi Collins; Mballa Mpouel, Marie-Laure; Djikeussi, Tatiana; Tchounga, Boris Kevin; Ayuk Ngwese, Derrick Tambe; et al. (Frontiers in Public Health, 2024)
Introduction An increased incidence of human Monkeypox (Mpox) cases was recently observed worldwide, including in Cameroon. To ensure efficient preparedness and interventions in the health system, we sought to assess the knowledge of Mpox's transmission, prevention, and response among healthcare workers (HCWs) in Cameroon. Methods A cross-sectional online survey was conducted among HCWs in Cameroon using 21-item questions adapted from the United States Centers for Disease Control and Prevention (US-CDC) standard questionnaire on Mpox. The overall knowledge of Mpox was assessed by cumulative score and categorized as excellent (≥80%, 17/21) or good (≥70%, ≥15/21) knowledge. The regression analysis was used to identify the predictors of Mpox knowledge. Results The survey enrolled 377 participants, but only responses from 342 participants were analyzed. Overall, 50.6% were female participants, and 59.6% aged 30 years or younger. The majority of the participants were medical doctors (50.3%); most worked in central-level hospitals (25.1%) and had 1–5 years of experience (70.7%). A total of up to 92.7% were aware of Mpox, with social media (58.7%) and radio/television (49.2%) as the main sources. The mean knowledge score was 14.0 ± 3.0 (4 to 20), with only 12.9% having excellent knowledge (≥80%) and 42.1% having good knowledge of Mpox. Younger age (26–30 years old) was associated with good knowledge, while workplace type was associated with excellent knowledge of Mpox (aOR [95% CI]: 4.01 [1.43–11.24]). Knowledge of treatment/management of Mpox was generally poor across the different professional categories. Conclusion Knowledge of Mpox among HCWs is substandard across different professionals. Thus, for optimal preparedness and immediate interventions for Mpox and similar emerging pathogens, capacity-strengthening programs should be organized for HCWs while encouraging scientific literature and organizational social media websites.